ANALISIS HAMBATAN GURU DALAM PENGIMPLEMENTASIAN PEMBELAJARAN TEMATIK DI ERA PANDEMI COVID19 - Savira Oktaviani; Galih Istiningsih (Khazanah Pendidikan, 2021)
This study aims to determine teacher barriers in thematic learning in the era of the Covid19 pandemic.This research was conducted in Soroyudan Public Elementary School, Tegalrejo district, Magelang regency. This research was conducted using data collection methods in the form of interviews conducted with principal, teachers, and students, observations to teachers and students, as well as examining some supporting documents. This research uses a qualitative approach to the type of case study. Test the validity of the data using triangulation techniques. Triangulation used is source triangulation, techciques triangulation and time triangulation.The results of this study were obtained analysis of teacher barriers in thematic learning in the era covid19 pandemic. The barriers in the initial activity was low internet network access, there are 16,9% of student who do not have smartphone, and there are 9% of parents who cannot use smartphone. The barriers in the core activity was low internet network access, there are 16,9% of student who do not have smartphone, there are 9% of parents who cannot use smartphone and limitations of the learning method used by teacher. Barriers in the final activity was low internet network access, there are 16,9% of student who do not have smartphone, and there are 9% of parents who cannot use smartphoneKeywords: Teacher Barriers, Thematic Learning, Covid19 Pandemic